THE STUDENTS’ ABILITY IN UNDERSTANDING LISTENING QUESTION RESPONSE IN TOEIC TEST - Kurniawan Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2016)
The purpose of this research was to determine the extent of students' skills inlistening comprehension in response to a question on the seventh semester student of theFaculty of Teaching and Education English Lancang Kuning University Pekanbaru. Theimportance of these tests is to megidentifikasi readiness of students in mastering the Englishlanguage to be used in the working world of international working environment. Thisresearch was conducted by survey method as a design. Participants in this study were fiftytwostudents, an instrument that researchers use in this research is to give thirty-questionmultiple-choice questions about the response. The results of this study showed that fifty-twostudents can be seen that the total overall value is 3040, the value of recurring middle value53.3 and 60. Values range from low to high at 23.3 from 93.3. After calculation, the averagestudent's ability to respond to questions is 58.46. In other words, the ability of students tounderstand listening to respond to questions categorized as low.